Effects of intramuscular vatinoxan (MK-467), co-administered with medetomidine and butorphanol, on cardiopulmonary and anaesthetic effects of intravenous ketamine in dogs - Vainio O.; Turunen H.; Raekallio M.; Honkavaara J.; Jaakkola J.; Scheinin M.; Männikkö S.; Hautajärvi H.; Bennett R. (Association of Veterinary Anaesthetists and American College of Veterinary Anesthesia and Analgesia, 2022)
Objective To investigate the impact of intramuscular (IM)co-administration of the peripheral α2-adrenoceptor agonist vatinoxan (MK-467) with medetomidine and butorphanol prior to intravenous (IV) ketamine on the cardiopulmonaryand anaesthetic effects in dogs, followed by atipamezole reversal.
Study design Randomized, masked crossover study.
Animals A total of eight purpose-bred Beagle dogs aged 3 years.
Methods Each dog was instrumented and administered two treatments 2 weeks apart: medetomidine (20 µg kg-1) and butorphanol (100 µg kg-1) premedication with vatinoxan (500 µg kg-1; treatment MVB) or without vatinoxan (treatment MB) IM 20 minutes before IV ketamine (4 mg kg-1). Atipamezole (100 µg kg-1) was administered IM 60 minutes after ketamine. Heart rate (HR), mean arterial (MAP) and central venous (CVP) pressures and cardiac output (CO) were measured; cardiac (CI) and systemic vascular resistance (SVRI) indices were calculated before and 10 minutes after MVB or MB, and 10, 25, 40, 55, 70 and 100 minutes after ketamine. Data were analysed with repeated measures analysis of covariance models. A p-value <0.05 was considered statistically significant. Sedation, induction, intubation and recovery scores were assessed.
Results At most time points, HR and CI were significantly higher, and SVRI and CVP significantly lower with MVB than with MB. With both treatments, SVRI and MAP decreased after ketamine, whereas HR and CI increased. MAP was significantly lower with MVB than with MB; mild hypotension (57-59 mmHg) was recorded in two dogs with MVB prior to atipamezole administration. Sedation, induction, intubation and recovery scores were not different between treatments, but intolerance to the endotracheal tube was observed earlier with MVB.
Conclusions and clinical relevance Haemodynamic performance was improved by vatinoxan co-administration with medetomidine-butorphanol, before and after ketamine administration. However, vatinoxan was associated with mild hypotension after ketamine with the dose used in this  study.  Vatinoxan  shortened  the  duration  of anaesthesia.